Pengaruh Pengetahuan, Pengawasan dan Kelengkapan Sarana Pengelolaan Sampah Awak Kapal terhadap Perilaku Pencegahan Pencemaran Laut di Pelabuhan - Nursyamsu Nursyamsu; Ade Mardani Putra; Astri Kustina Dewi; Henni Sutryani (Universitas Muhammadiyah Yogyakarta, 2022)
In Indonesia, marine pollution is a common problem. Ship personnel operating in ports often contribute to marine pollution. This study aimed to determine the impact of crew behavior in relation to the prevention of marine pollution on their knowledge, supervision, and completeness of their waste management facilities. The methodology of this research is quantitative. With the help of SmartPLS version 3.0, the analysis used in this work takes a structural approach to the Equation Model. A total of fifty crew members who participated in the study were randomly selected from the pool of participants. In addition, participants in this study were randomly selected by distributing questionnaires to the crew at Merak Harbor. According to research findings, the behavior of seafarers in preventing marine pollution in ports is influenced by their knowledge, supervision, and quality of infrastructure.